2018
DOI: 10.1016/j.jadohealth.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and Variation in School-Level Youth Sports Traumatic Brain Injury Policy Content

Abstract: All 71 TBI policies covered at least two of the three youth sports TBI law tenets, but with considerable variation. Future research should assess variations by schools within the same state and their impact on TBI rates in school athletics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
(30 reference statements)
1
29
1
Order By: Relevance
“…Detailed information on recruitment, sample size, and data-collection procedures are reported elsewhere. 9 For the purposes of this study, only interviews from ATs were included and reported.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information on recruitment, sample size, and data-collection procedures are reported elsewhere. 9 For the purposes of this study, only interviews from ATs were included and reported.…”
Section: Data Collectionmentioning
confidence: 99%
“…20 They were uniquely positioned to implement return-to-play protocols and to contribute to return-to-play decisions due to their presence on staff, their background and training, and their personal knowledge of individual athletes' typical demeanor. 9 In addition, many states allow ATs to provide return-to-play clearance to concussed athletes. Often, although physicians are designated to provide clearance, an AT may override this decision and keep an athlete out of play longer.…”
Section: Tenet 2: Return To Playmentioning
confidence: 99%
“…Conversely, the rest of the state laws made education optional, required only receipt of an information sheet about concussion, did not specify educational requirements, or lacked any reference to coach education related to concussions . At least one study suggests formal coach training related to concussions is uncommon . That study found that among 71 high schools, only one‐third had policies requiring formal education for coaches that addressed the recognition and management of concussion.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…For example, some laws do not specify what athletes should be taught about concussion, and fewer than half of states require the inclusion of information about the risk of continuing to play after a concussion . Additionally, as mentioned previously, not all states require education for coaches . Therefore, schools and school districts seeking to reduce concussion risks and improve response to concussions may consider developing policies and practices beyond what is outlined in the legislation.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…Previous studies have identified variations in the content 5,6 and implementation 7,8 of high school policies or state laws. In one national study of high schools participating in a nationwide sports injury surveillance program, all policies included at least 2 of the 3 key SRC law tenets, with the distribution of education information sheets only being included in 59.2% of the policies.…”
mentioning
confidence: 99%